Yesus Mengutuk Pohon Ara Berdasarkan Matius 21:18-22 dan Implikasinya Bagi Orang Percaya Masa Kini - Buyi, Julianus; Lele, Aldorio Flavius (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2021)
The purpose of this article is to find out the meaning of Jesus cursed the fig tree based on Matthew 21:18-22 and the implications for those who believe today. This study uses qualitative research methods with inductive reasoning and the application of biblical hermeneutic principles and methods (biblical interpretation). The conclusion of this article is, Jesus' curse on the fig tree is a symbol and lesson of faith. Some of the differences found in Matthew and Mark occur because of differences in writing contexts and different purposes, a life that produces fruit, a life with a pure heart, a life that cares about the environment, and a life that relies on God.